2023
DOI: 10.3390/diagnostics13030496
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiac-Pulsatility-Induced Displacement and Geometry Changes between the Cook ZBIS and Gore IBE: Postoperative Comparison Using ECG-Gated CTA Scans

Abstract: To what extent the stentgraft design of iliac branch devices (IBDs) relates to dynamic deformation is currently unknown. Therefore, this study aimed to quantify and compare displacement and geometry changes during the cardiac cycle of two common IBDs. This paper presents a two-center trial with patients treated with a Zenith bifurcated iliac side (ZBIS) or Gore iliac branch endoprosthesis (IBE). All patients underwent a retrospective electrocardiogram (ECG)-gated computed tomographic angiography (CTA) during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The dynamic behavior of stent grafts in the aorta has been reported in literature, 3 , 4 , 9 , 13 , 21 , 22 , 23 , 24 including papers that have implemented the same image registration and segmentation techniques as applied in the present study. 3 , 4 , 13 , 21 , 22 Validation of these algorithms has been performed by Koenrades et al, 2 including accuracy assessment for motion calculation in ECG-gated CT scans with reconstructions into 10 phases on CT scanners from two vendors (Somatom Definition Flash as used in the current study and the Aquilion 64, Toshiba Medical Systems Corporation, Otawara City, Tochigi Prefecture, Japan). For this validation, they used an experimental setup and found an absolute error of at most 0.3 mm for motion calculation, with average errors of 0.12 and 0.14 mm for the respective scanners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic behavior of stent grafts in the aorta has been reported in literature, 3 , 4 , 9 , 13 , 21 , 22 , 23 , 24 including papers that have implemented the same image registration and segmentation techniques as applied in the present study. 3 , 4 , 13 , 21 , 22 Validation of these algorithms has been performed by Koenrades et al, 2 including accuracy assessment for motion calculation in ECG-gated CT scans with reconstructions into 10 phases on CT scanners from two vendors (Somatom Definition Flash as used in the current study and the Aquilion 64, Toshiba Medical Systems Corporation, Otawara City, Tochigi Prefecture, Japan). For this validation, they used an experimental setup and found an absolute error of at most 0.3 mm for motion calculation, with average errors of 0.12 and 0.14 mm for the respective scanners.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, quantifying cardiac-pulsatility-induced motion with 8 or 10 phases in an ECG-gated CT angiography might be an undersampling of the motion signal, especially for reconstructions into 8 phases. For example, Simmering et al 13 investigated the postoperative behavior of 2 different iliac branched devices, scanned with different scanning protocols: reconstruction into 8 phases or 10 phases on a Philips Brilliance iCT 256 scanner. Initially, there may have been doubt as to whether the observed difference between the stent grafts was caused by the stent graft type or the scan type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, two research groups showed that standard CT angiography (CTA) alone does not suffice when attempting to understand the dynamics of the abdominal aorta that includes implanted stent grafts. In their retrospective series, Simmering and coworkers used electrocardiogram (ECG)-gated CTA to determine the geometry changes in two different types of iliac branch devices for the treatment of common iliac artery aneurysms [2]. In addition to the iliac arteries, ECG-gated CTA may be of great help to study the geometry changes in thoracic and abdominal aortic endografts during the cardiac cycle, their influence on cardiac function, as well as the (changed) compliance of the thoraco-abdominal aorta post endovascular repair of aortic aneurysms (EVAR).…”
mentioning
confidence: 99%